THE EFFECT OF MANAGERIAL OWNERSHIP AND INSTITUTIONAL OWNERSHIP ON DEBT POLICY : EVIDENCE FROM MANUFACTURING FIRM LISTED ON INDONESIA STOCK EXCHANGE - Muslim, Bintang Lazuardi Benteng Buana; Pamungkas, Leo Dadyo (Program Studi Manajemen, 2023)
This study was conducted to test variable impact managerial ownership and institutional ownership on debt policy. The study used the method purposive sampling. Some of the sample criteria or considerations used in the study are as follows: companies that fall under the manufacturing sector; companies that release financial reports for the years 2018 to 2022; excludes companies that underwent an initial public offering (IPO) and filed for bankruptcy between 2018 and 2022; and companies that have been in business for at least five years, so that a sample was obtained after being chosen using a sampling technique of 28 manufacturing companies listed on the Indonesia Stock Exchange (IDX). The data in this study were processed using Smart-PLS with partial equation modeling. The hypothesis testing method uses a significance level of 5%.The results showed that managerial ownership has no effect on debt policy and institutional ownership have a significance positive on debt policy.